Dynamic imaging of accommodation by swept‐source anterior segment optical coherence tomography. Issue 3 (March 2015) - Neri, Alberto; Ruggeri, Marco; Protti, Alessandra; Leaci, Rosachiara; Gandolfi, Stefano A.; Macaluso, Claudio
Abstract : Purpose : To study the accommodation process in normal eyes using a commercially available clinical system based on swept‐source anterior segment optical coherence tomography (AS‐OCT). Setting : Ophthalmology Department, University of Parma, Italy. Design : Evaluation of diagnostic technology. Methods : Right eyes were analyzed using swept‐source AS‐OCT (Casia SS‐1000). The optical vergence of the internal coaxial fixation target was adjusted during imaging to obtain monocular accommodation stimuli with different amplitudes (0, 3.0, 6.0, and 9.0 diopters [D]). Overlapping of real and conjugate OCT images enabled imaging of all the anterior segment optical surfaces in a single frame. Central corneal thickness (CCT), anterior chamber depth (ACD), and lens thickness were extracted from the OCT scans acquired at different static accommodation stimulus amplitudes. The crystalline lens was analyzed dynamically during accommodation and disaccommodation by acquiring sequential OCT images of the anterior segment at a rate of 8 frames per second. The lens thickness was extracted from the temporal sequence of OCT images and plotted as a function of time. Results : The study analyzed 14 eyes of 14 subjects aged 18 to 46 years. During accommodation, the decrease in the ACD was statistically significant ( P < .05), as were the increase in the lens thickness ( P < .001) and the slight movement forward of the lens central point ( P < .01). The CCT and anterior chamber width measurements did not change statistically significantly during accommodation. The lens thickness at 0 D was positively correlated with age ( P < .01). Conclusion : High‐resolution real‐time imaging and biometry of the accommodating anterior segment can be effectively performed using a commercially available swept‐source AS‐OCT clinical device. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.